PENANAMAN NILAI-NILAI MULTIKULTURAL DALAM MENGEMBANGKAN SIKAP TOLERANSI SOSIAL PADA SISWA KELAS V SDN 1 SINGKAWANG TENGAH - Adirah; Wasis Suprapto; Mertika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Instilling multicultural values is one of the methods used for cross-cultural learning by forming mindsets, attitudes, actions and habits so that Indonesian national awareness emerges. The research aims to find out: (1) the cultivation of multicultural values in developing social tolerance attitudes (2) factors that influence the cultivation of multicultural values in developing social tolerance attitudes. This research is a qualitative research, with observation, interview and documentation methods. The results of the study show that (1) the cultivation of multicultural values carried out by schools to develop social tolerance attitudes by applying them through learning in the classroom and outside the classroom as well as supervision during the school environment. The inculcation of multicultural values in the classroom can be done through the subject of Pancasila Education, it can also be through the arrangement of student seating in the classroom. While outside the classroom, it can be by holding extracurriculars, especially for scouts. As for supervision in the school environment, security guards play a role in guarding students, as well as teachers while at school; (2) There are 2 factors that affect the cultivation of structural values in developing social tolerance attitudes, namely, supporting factors and inhibiting factors. Supporting factors include school climate, extracurriculars, the role of teachers, facilities and infrastructure. Meanwhile, the inhibiting factors are ethnocentrism, stereotypes, bad prejudice, racism, discrimination and scapegoating.